The Examined Life : Family, Community, Work in American Literature - Miller, Jim Wayne (Appalachian State University, 1989)
Concerned with the 50% dropout rate for public high school students in the Southern Highlands, Jim Wayne Miller published this book in 1989 to ensure that young people had access to published works and other text that examine the themes of familiy, community, and work. Miller intended to provide public school teachers with the tools to engage students and stimulate meaningful conversations. Miller produced a work that guides students to reflect on their heritage, see the bigger picture, and develop a broader perspective of human existence.
English
Keywords: Regional studies; Social Science; Regional Studies